Hidrocarbonetos alifáticos em sedimentos de fundo do estuário do Rio Potengi, grande Natal (RN): implicações ambientais - Carrascoza, Lígia Soares (2011)
The Potengi river estuary is located in the region of Natal (RN, Brazil), comprising a population of approximately 1,000,000 inhabitants. Besides the dominant urban presence, the estuary has fragments of mangrove forest. The objective of this study is to determine the aliphatic hydrocarbons found in the bottom sediments of this estuary, identifying their levels, distribution and their possible origins through the diagnostic rates, indexes and results comparisons with the local anthropic and natural characteristics. The samples were obtained according to a plan that allowed sampling of the estuary up to 12 km upstream from it as mounth. 36 stations were selected, grouped into 12 cross sections through the course of the river and spaced on average by 1 km. Each section consisted of three stations: the right margin, the deepest point and the left margin. The hydrocarbon n-alkanes from C10 to C36, the isoprenoids pristane and phytane, the unresolved complex mixture (UCM) and the total resolved hydrocarbons were analyzed by gas chromatography. N-alkanes, pristane, phytane and UCM were detected only at some stations. In the other, the concentration was below the detection limit defined by the analytical method (0.1 mg / kg), preventing them from being analyzed to determine the origin of the material found. By using different parameters, the results show that the estuary receives both the input of petrogenic hydrocarbons, but also of biogenic hydrocarbons, featuring a mixture of sources and relatively impacted portions. Based on the characteristics and activities found in the region, it is possible to affirm that petrogenic sources related to oil products enter the estuary via urban runoff or boats traffic, boat washing and fueling. Turning to the biogenic source, the predominant origin was terrestrial, characterized by vascular plants, indicating contribution of mangrove vegetation. It was evident the presence of, at specific points in the estuary, hydrocarbon pollution, and, therefore is recommended the adoption of actions aimed at interrupting or, at least, mitigating the sources potentially capable of damp petrogenic hydrocarbons in the estuary studied.